Mediatization of Care for MSM Living with HIV by Government and Civil Society Organizations in the Philippines during the COVID-19 Pandemic - Solis, Randy Jay C. (Archīum Ateneo, 2024)
In the modern milieu, information and communications technologies (ICT) developments have dominated and been domesticated in almost all aspects of human life. This movement was made more palpable during the recent COVID-19 pandemic when access to regular treatment has been disrupted for people living with the human immunodeficiency virus (PLHIV). The health sector had to cope with the “new normal” by migrating to the online sphere. This phenomenon may be understood as mediatization, where media are viewed as an independent institution with its norms and logics, influencing the health service sector. To understand the reconfigured communicative practices of government and non-government organizations in PLHIV care provision, this study asked: How is care mediatized, and what are its consequences on healthcare service provision for men having sex with men (MSM) living with HIV in the Philippines? Narratives of interviewees from organizations enacting the online care continuum for PLHIVs reveal that, on an individual level, media and technologies have been embedded in the communicative practices of health service providers. On an institutional level, media logics are now part and parcel of the practice of health provision for PLHIVs. Examining the consequences of the mediatization of PLHIV care, theoretical and practical recommendations are made at the end of the study.